Superantigenos : una particular interaccion entre microorganismos y el sistema inmune - Antúnez, María Inés (1997)
Fil: Antúnez, María Inés. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.